2022
DOI: 10.14719/pst.1814
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of stable lentil genotypes through genotype by environment interactions on yield potential in Morocco

Abstract: Genotype by environment (G×E) interaction study becomes essential for selecting high and stable yielding genotypes. Altogether 64 lentil genotypes representing improved varieties, landraces and advanced lines were evaluated under 6 environments for green cover, phenological characters, grain yield and 1000 seed weight. Variance analysis revealed highly significant effects of genotype, environment and genotype by environment interaction for all studied traits. The environment had the greatest effect with 75.7% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…In the present study, grain yield was significantly influenced by the genotype at Sidi El Aidi, while this effect was not significant at Adana in both seasons (Table S6). Combined analysis of variance across environments revealed that grain yield was significantly affected by genotype, environment, and their interaction (Table S10); in the same sense similar results have been reported previously (Mohebodini et al 2006;Sabaghnia et al 2008;Mohammed et al 2016;Abbas et al 2019;Idrissi et al 2019;Chen et al 2022;Baggar et al 2023b, a;Ghaffar et al 2023;Hossain et al 2023).…”
Section: Phenotypic Variability For Relevant Agronomic Traits In Diff...supporting
confidence: 87%
See 2 more Smart Citations
“…In the present study, grain yield was significantly influenced by the genotype at Sidi El Aidi, while this effect was not significant at Adana in both seasons (Table S6). Combined analysis of variance across environments revealed that grain yield was significantly affected by genotype, environment, and their interaction (Table S10); in the same sense similar results have been reported previously (Mohebodini et al 2006;Sabaghnia et al 2008;Mohammed et al 2016;Abbas et al 2019;Idrissi et al 2019;Chen et al 2022;Baggar et al 2023b, a;Ghaffar et al 2023;Hossain et al 2023).…”
Section: Phenotypic Variability For Relevant Agronomic Traits In Diff...supporting
confidence: 87%
“…In accordance with these results, previous studies reported the variation of hundred-seed weight according to the genotype and environmental conditions (El haddad et al 2020;Choukri et al 2020). In addition, other investigations, as in the present study, indicated that hundred-seed weight in lentil is not significantly affected by genotype × environment interaction (Abo-Hegazy et al 2013); however, other researchers reported that this effect was statistically significant (Bermejo et al 2020;Baggar et al 2023a). Additionally, significant variation has been reported for hundred-seed weight between and within yellow and red-cotyledon types, with ranges of 1.7-7.4 g for yellow-cotyledon types and 1.3-5.2 g for red-cotyledon types (Tullu et al 2001).…”
Section: Phenotypic Variability For Relevant Agronomic Traits In Diff...supporting
confidence: 44%
See 1 more Smart Citation
“…According to Oladosu et al 30 , the size of each environment vector indicates its ability (distinctiveness) to distinguish between genotypes inside that particular environment. Using GGE biplot analysis, distinct environments (E3 and E5) were found to be discriminative and representative for the yield and presence of particular minerals, such as manganese and zinc 4 .…”
Section: Resultsmentioning
confidence: 99%